Power efficiency in broadband wireless communications - Varahram, Pooria; Mohammady, Somayeh; Mohd Ali, Borhanuddin; Sulaiman, Nasri (CRC Press, 2014)
Power Efficiency in Broadband Wireless Communications focuses on the improvement of power efficiency in wireless communication systems, especially of mobile devices. Reviewing cutting-edge techniques for conserving power and boosting power efficiency, the book examines various technologies and their impact on consumer devices. It considers each technology, first by introducing the main physical layer components in recent wireless communication systems along with their shortcomings, and then proposing solutions for overcoming these shortcomings.